Climate-sensitive health counselling: a quantitative survey on addressing climate change: Nicola Krippl. (25th October 2022) - Krippl, N; Mezger, NCS; Fischer, H; Schildmann, J; Mikolajczyk, R; Danquah, I; Kantelhardt, EJ; Herrmann, A
Abstract: Background: Climate change and its mitigation have significant health implications. Hence, medical associations call on physicians to inform the population about health risks of climate change and possible health co-benefits of climate action. However, so far it is unclear what preferences the general public has about climate-sensitive health counselling (CSHC). Therefore, we developed a survey tool to a) characterize experiences of CSHC, b) identify preferences about communication methods and themes, and c) determine associations of socioeconomic characteristics and climate change attitudes with CSHC preferences. Methods: The tool development for this cross-sectional online-based survey was embedded in a bigger research project on the conceptualization of CSHC, which follows an exploratory mixed-methods design. Results of preceding qualitative interviews about CSHC were integrated into the tool development. After two pilot tests, the tool was administered from April to June 2022 through the population-based HeReCa panel (Health Related Beliefs and Health Care Experiences in Germany), comprising 3200 participants from 5 federal states. Sociodemographic data is available for all participants. Results: The final tool entails 46 items, sorted into 7 sections. Two sections serve as dependent variables for the association analysis: 13 items about the acceptability of different communicative approaches of CSHC and 18 items on preferences for themes in CSHC. Three sections serve as independent variables for the analysis: attitudes on climate change, level of engagement, and sociodemographic data. Two sections assess experiences with CSHC and preferred information channels to serve as descriptive results. Conclusions: A rigorous methodology proved helpful for survey development within a mixed methods study. In triangulation with qualitative data, results of the survey will help physicians to deliver CSHC tailored to the preferences of different sociodemographic groups. Key messages: We developed a survey tool to measure the general public's preferences regarding climate-sensitive health counselling (CSHC) of physicians. Our study will provide guidance for physicians on how to offer CSHC to specific patient subgroups based on socioeconomic characteristics and attitudes towards climate change.